Fathers' Commute to Work and Children's Social and Emotional Well-Being in Germany - Jianghong Li; Matthias Pollmann-Schult (Journal of Family and Economic Issues, 2016)
Using the German Socio-Economic Panel study, we addressed the main question: Is fathers' commute to work associated with increases in child social and emotional well-being as measured in Strengths and Difficulties Questionnaires? If so, would this association be mediated by reduced time spent with children or moderated by change in family income due to commuting? The findings show that fathers' daily commute to work was associated with more peer relationship problems, and it also appeared to be linked to more emotional symptoms and greater hyperactivity in children. Fathers' weekly commute was also linked to child emotional problems. The likelihood of having peer relationship problems in children increased with the distance of fathers' daily commute to work. This is one of only two studies on this important topic and much further research is warranted.
Keywords: 330; child social-emotional well-being; commuting to work; fathers; Germany; SDQ; SOEP